Competition with Variety Seeking and Habitual Consumption: Price Commitment or Quality Commitment?. (6th March 2017) - Xiong, Liyang; Liu, Guan; Jiang, Shi
Abstract : This paper investigates price and quality competition in a market where consumers seek variety and habit formation. Variety seeking is modeled as a decrease in the willingness to pay for product purchased on the previous occasion while habitual consumption may increase future marginal utility. We compare two competing strategies: price commitment and quality commitment. With a three-stage Hotelling-type model, we show that variety seeking intensifies while habitual consumption softens the competition. With price commitment, firms supply lower quality levels in period 1 and higher quality levels in period 2, while, with quality commitment, firms charge higher prices in period 1 and lower prices in period 2. However, the habitual consumption brings the opposite effect. In addition, with quality commitment variety seeking leads to a lower profit and a higher consumer surplus, while habitual consumption leads to the opposite results. On the other side, with price commitment these behaviors have no effect on the consumer surplus, although they still lower down the firm profits. Finally, we also identify conditions under which one strategy outperforms the other.